Long memory in the Croatian and Hungarian stock market returns - Silvo Dajčman; Mejra Festić; Alenka Kavkler (Zbornik radova Ekonomskog fakulteta u Rijeci : časopis za ekonomsku teoriju i praksu, 2012)
The objective of this paper is to analyze and compare the fractal structure of the Croatian and Hungarian stock market returns. The presence of long memory components in asset returns provides evidence against the weak-form of stock market efficiency. The starting working hypothesis that there is no long memory in the Croatian and Hungarian stock market returns is tested by applying the Kwiatkowski-Phillips-Schmidt-Shin (KPSS) (1992) test, Lo’s (1991) modified rescaled range (R/S) test, and the wavelet ordinary least squares (WOLS) estimator of Jensen (1999). The research showed that the WOLS estimator may lead to different conclusions regarding long memory presence in the stock returns from the KPSS and unit root tests or Lo’s R/S test. Furthermore, it proved that the fractal structure of individual stock returns may be masked in aggregated stock market returns (i.e. in returns of stock index). The main finding of the paper is that both the Croatian stock index Crobex and individual stocks in this index exhibit long memory. Long memory is identified for some stocks in the Hungarian stock market as well, but not for the stock market index BUX. Based on the results of the long memory tests, it can be concluded that while the Hungarian stock market is weakform efficient, the Croatian stock market is not.